Agrometeorology 2021
DOI: 10.5772/intechopen.95893
|View full text |Cite
|
Sign up to set email alerts
|

Climate as the Major Factor Controlling Phenology

Abstract: The witnessed aberrance and irregularities in the timing of pheno-phases is an undeniable evidence of the reality of the climate change and hence proves the complete control of climate over phenology. In fact, some researchers mentioned the advance of blooming and the delay of defoliation to the mid of winter as well as the disappearance of many animal and vegetal species. This would visibly illustrates the impact of climate changes which became a factual reality. These facts a long with the rhythmicity of lif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…In addition, on 2020 cumulative rainfall were significant poorer respect to the other two years, which, added to the low temperatures, caused all the floral expression to be delayed and some button flowers were lost due to death. In coincidence with Guesmi (2021), it can be said phenology is directly influenced and controlled by climate especially by duration of sunlight, precipitation, temperature and other life-controlling factors. In fact, between results observed on 2018 and the others two years studied, one month advance was occurred of the anthesis stage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, on 2020 cumulative rainfall were significant poorer respect to the other two years, which, added to the low temperatures, caused all the floral expression to be delayed and some button flowers were lost due to death. In coincidence with Guesmi (2021), it can be said phenology is directly influenced and controlled by climate especially by duration of sunlight, precipitation, temperature and other life-controlling factors. In fact, between results observed on 2018 and the others two years studied, one month advance was occurred of the anthesis stage.…”
Section: Discussionmentioning
confidence: 99%
“…The timing of phenological events such as bud burst, leaf-expansion, abscission, flowering, fertilization, seed set, fruiting, seed dispersal and germination can be quite sensitive to environmental conditions mainly climatic, being temperature, solar radiation, and water availability the key of factors that control plant phenology (Guesmi, 2021). Study of reproductive phenology and its interactions with the ecosystem provides the necessary tools for understanding the biology of a species (Kebede and Isotalo, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Wetland has been described as a 'kidney of landscape' (Sun, 2018) [1] . Wetlands are areas where water is the primary factor controlling the environment and the associated plant and animal life (Guesmi, 2021) [59] . The wetlands are the most productive ecosystems on the Earth (Ghermandi et al, 2008) [2] and they provide many beneficial services to human society (Brink et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The increment of atmospheric (CO 2 ) is the main factor of changes in temperature and precipitation, and it can also affect changes in phenology directly [5,10]. The effect of elevated (CO 2 ) on the vegetative and reproductive growth of Xanthium strumarium was studied, and it was found that the vegetative growth increased with an extension of the flowering period when the plants were exposed to elevated CO 2 [11].…”
Section: Introductionmentioning
confidence: 99%